Dose-response and temporal ergogenic effects of ginseng supplementation in athletes and active participants: A systematic review and meta-analysis. Issue 21 (2nd November 2022) - Khan, Nasreen; Sharma, Saurabh; Dahiya, Indu; Khan, Junaid; Sharma, Shalini; Sharma, Raj Kumar
ABSTRACT: This review sought to assess the dose-response, i.e., low (<300 mg/day) and high (>300 mg/day), and temporal effects of ginseng, i.e., immediate, short-term (up to 4 weeks) and long-term (>4 weeks) in comparison to placebo on physical performance [visual analogue scale (VAS) level, vertical jump(VJ), rating of perceived exertion (RPE), peak power output (PPO)] and physiological measures [VO2 max, creatine kinase(CK), heart rate(HR)], in athletes and active participants. Search in four databases with English language constraints yielded 492 studies. Fourteen studies were shortlisted through PEDro scale by methodological quality evaluation. Ginseng exhibited significant short-term effect at high dosage for VJ improvement (SMD: −8.17, 95% CI: −16.28 to −0.06, p= 0.05). Ginseng had no effect on VAS (SMD: −0.65, 95% CI: −1.35 to 0.06, p= 0.07), RPE (SMD: −1.11, 95% CI: −2.57 to 0.35, p= 0.14), PPO (SMD: −0.70, 95% CI: −1.78 to 0.38, p= 0.20), HR (SMD: −0.54, 95% CI: −2.05 to 0.96, p= 0.48), CK (SMD: 0.33, 95% CI: −0.18 to 0.84, p= 0.21) and VO2 max (SMD: 0.08, 95% CI: −0.69 to 0.85, p= 0.08).The ginseng supplementation was found to have significant short-term effect at high dose only for VJ in athletic and active participants. Methodologically strong research is warranted to further consolidate these findings.